Odgovornost za štetu prouzročenu trećim osobama obavljanjem zakonske revizije - Mićović, Miodrag (Array, 2018)
The authors deal with the issue of possible liability of auditors for damage caused to third parties (shareholders, creditors, potential investors...) by performing a statutory audit. They present some of the comparative solutions to these issues and the changes at the European jurisdiction caused by major financial scandals at the beginning of this century. The main objective of Directive 2014/56 / EU is to strengthen the public-law supervision of auditors and their services, which should enhance the quality of their services and the confidence of third parties in their work. There are a number of rules of auditor’s professional standards and ethical rules, raised to the level of regulation. The professional skepticism and independence of auditors, the underlying assumption that the auditor’s opinion is not misleading, are particularly pronounced. The professional skepticism and independence of auditors are particularly pronounced, the underlying assumption that the auditor’s opinion is not misleading. However, the responsibility for providing financial information is at the management of the audited entities, and the auditors only actively question this information, not affirming them. Third parties are often unaware of the limitations of an audit which lead to an expectation gap. In Croatia there are no specific rules on auditors’ liability for damage and according to general rules liability is unlimited, to the audited company and to third parties.